2019
DOI: 10.1073/pnas.1917513116
|View full text |Cite
|
Sign up to set email alerts
|

Probing predatory bacteria as an antibacterial remedy

Abstract: Researchers have started to evaluate predatory bacteria such as Bdellovibrio-shown here in a false-color transmission electron microscopy image at 50,000× magnification-as a means of treating intractable, antibiotic-resistant infections. Image credit: Science Source/ALFRED PASIEKA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…ASV’s analysis of the three sponges, M. ( Oxymycale ) acerata , H. pilosus and H. ( Rhizoniera ) dancoi , displayed Deltaproteobacteria ( Figure 2 ; Tables S5–S7 ) belonging to the phylum Proteobacteria, that, as mentioned above, produce interesting bioactive metabolites [ 57 ]. For instance, H. pilosus exhibited some strains included into the genus Bdellovibrio ( Figure 3 ; Table S7 ), which is an obligate predator of other Gram-negative bacteria that was proposed for possible biotechnological applications toward medicinal, agricultural and industrial fields [ 113 , 114 , 115 ].…”
Section: Discussionmentioning
confidence: 99%
“…ASV’s analysis of the three sponges, M. ( Oxymycale ) acerata , H. pilosus and H. ( Rhizoniera ) dancoi , displayed Deltaproteobacteria ( Figure 2 ; Tables S5–S7 ) belonging to the phylum Proteobacteria, that, as mentioned above, produce interesting bioactive metabolites [ 57 ]. For instance, H. pilosus exhibited some strains included into the genus Bdellovibrio ( Figure 3 ; Table S7 ), which is an obligate predator of other Gram-negative bacteria that was proposed for possible biotechnological applications toward medicinal, agricultural and industrial fields [ 113 , 114 , 115 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obligate predatory bacteria, including Bdellovibrio bacteriovorus and Micavibrio aeruginosavorus , populate soils and water globally [ 87 ]. Epibiotic or endobiotic predatory bacteria are attached to the membrane of the Gram-negative bacteria to consume prey contents and divide outside or inside their prey [ 88 , 89 , 90 ]. Several studies have demonstrated that B. bacteriovorus can kill more than 100 human bacterial pathogens acting as “living antibiotic” [ 91 ].…”
Section: Alternative Strategies To Combat Antibiotic Resistancementioning
confidence: 99%
“…Moreover, the relatively benign occupancy of macrophages by Bdellovibrio could prevent other intracellular pathogens from entering. However, this passive uptake suggests that macrophages might present predatory bacteria to antibody-forming cells and, consequently, humans could develop immune reactions against them after repeated exposures [30] . In fact, Raghunathan et al .…”
Section: Balos As Biocontrol Agentsmentioning
confidence: 99%
“…Predatory bacteria play an essential role in these new lines of research [16] , [28] , [29] , [30] , [31] . The fact that these micropredators are designed to lyse and kill other bacteria, including MDRB and those pathogens that form biofilms, has led to them being proposed as a reasonable antibiotic alternative to be explored.…”
Section: Introductionmentioning
confidence: 99%